Stress management that reflect job satisfaction in Marketing Department Nestle Products Sdn Bhd / Mohd Mu'azam Shah Abdul Mutalib (Faculty of Business Management, 2007)
The important of stress management in any organization is growing to ensure employee job satisfaction. This will help organization to identify several stress problems that normally occur during working. There are three elements that need to be focus which are workload, working environment and conflict which determine the stress factor. Moreover, this research also utilized a simple random sampling technique which is pilot study and distribution of questionnaire to understand the stress related factor that causes stress among the employees of Marketing Department Nestle Products Sdn. Bhd. The findings highlighted the workload, working environment and conflict plays major role in reflecting the stress management in the organizations. Most respondent say that they experiencing or feels stress to the stress factor. In other hands, the challenge of the researcher is to find the factor that cause stress and give good solution to the problems. Future research is proposed and it should be conducted to all employees in the organization. This will help the organization to prevent the stress before it's become worse and reflect the job satisfaction among employees. This research also identifies the stress symptoms that occur during working. This is important to Nestle Product Sdn, Bhd. to take corrective action in order to achieve employee's satisfaction. Based on conclusion, the researcher concludes that stress occur in the organization although the management have already trying to reduce stress. It also found that although the employees experiencing stress while working they still enjoy working in the organizations. Finally, preventive stress management can help to reduce the stress among employees in Marketing Department Nestle Products Sdn. Bhd.